ANALISIS PENGARUH STRES KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWANPT INDOMARCO ADI PRIMA TEGAL - Saputri, Rahayu Eka; Barima, Hima; Supriatin, Dyah (DFAME Digital Financial Accounting Management Economics Journal, 2024)
The company must pay attention to employee performance in optimizing human resources. The decline in performance that occurs at PT Indomarco Adi Prima Tegal can be influenced by work stress and work environment as factors that influence employee performance. This research aims to analyze the influence of the work stress and work environment on the performance of employees at PT Indomarco Adi Prima in Tegal. This research is descriptive in nature, using a quantitative analysis method. The research object is the employees of PT Indomarco Adi Prima in Tegal, with the sample in this research consists of 45 employees using total sampling technique. The data collection technique used in this research is the questionnaire method. Data analysis will employ Multiple Linear Regression analysis, t-test, F-test, and Coefficient of Determination test. The data analysis results using the t-test indicate that the work stress has a negative and significant influence on the performance of employees at PT Indomarco Adi Prima in Tegal, with a calculated t-value of -3,097 > 2,018 and a significance level of 0.003 < 0.050. Work environment has a positive and significant effect on the performance of employees at PT Indomarco Adi Prima in Tegal, with a t-value of 5,664 > 2,018 and a significance level of 0.000 < 0.050. The results of the data analysis using the F-test show that the work stress and work environment simultaneously have an effect on the performance of employees at PT Indomarco Adi Prima in Tegal, with an F-value of 174,910 > 3,23 and a significance level of 0.000 < 0.050. The results of the Coefficient of Determination analysis yielded an Adjusted R-Square value of 0.888, indicating that the work stress and work environment can account for 88.8% of the variation in performance. The remaining 12.2% is influenced by other factors not included in this research.